Primary Gastric Lymphoma Presenting as Acute Pancreatitis: A Case Report - Raj, Mithun; Ghoshal, Uday C; Choudhuri, Gourdas; Mohindra, Samir (JOP. Journal of the Pancreas, 2013)
Context Diffuse large B-cell lymphoma is the commonest form of non-Hodgkin lymphoma. Gastro-intestinal tract and bone marrow are common extra-nodal sites of lymphomatous involvement. Case report A 54-year-old woman presented with acute onset epigastric pain. On evaluation, raised serum amylase and radiological features of acute pancreatitis were detected. Gastroscopy revealed thickened folds in distal stomach, which on histopathology revealed large B-cell lymphoma. Subsequently, the patient developed extra-hepatic biliary obstruction due to peripancreatic lymph nodal mass that was relieved with plastic biliary stenting. Subsequent chemotherapy regime directed against lymphoma led to resolution of lymphoma. Conclusion In this patient , pancreatitis was the initial presentation of primary gastric lymphoma, which has not been commonly reported and therefore should be considered in the etiological workup. Image: Thickened gastric folds in distal body.